Pengaruh Persepsi Keamanan, Kualitas Informasi dan Kepercayaan terhadap Keputusan Pembelian Online : Studi Kasus pada Konsumen Shopee di Kota Lhokseumawe - Harjoni Desky; Rina Murinda; Razali Razali (Owner : Riset dan Jurnal Akuntansi, 2022)
Trade through electronic media (e-commerce) is currently increasingly mushrooming in Indonesia. This study aims to analyze the partial and simultaneous effect of the variables perceived security, quality of information and trust on the purchasing decisions of shopee consumers in Lhokseumawe city. The research method used is descriptive quantitative method, there are two research data, namely primary data and secondary data which are designed comprehensively to answer the hypotheses built, namely to determine the effect of Security Perception, Information Quality and Trust on online shopee consumer purchasing decisions in Lhokseumawe City. The population in this study were all Shopee consumers in Lhokseumawe City and the research sample was determined by probability sampling, totaling 100 samples. This study used multiple linear regression analysis, and data processing was carried out using SPSS version 20.0 for validity, reliability, and multiple linear regression. The results of the study concluded that simultaneously perceived security, information quality and trustworthiness had an effect on purchasing decisions, while partially security perceptions had no effect on purchasing decisions, while information quality had an effect on purchasing decisions.